Causal Factors Influencing Loyalty to Buying Cosmetics with Mutelu Beliefs on Facebook Pages of Consumers in Bangkok and Metropolitan Areas - Srikasame, Noppon; Srisa-an, Chetneti; Saelee, Rattanaporn (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Nowadays personal belief and beauty product have been combined and led to a “Mutelu" (spiritual belief-based) cosmetics market gaining significant popularity on social media platforms. Amidst the rapid expansion of e-commerce, consumer loyalty has become a key factor in competitive benefit. This research article aims to investigate the causal factors influencing consumer loyalty toward purchasing Mutelu cosmetics via Facebook pages among consumers in Bangkok and its vicinity. Employing a quantitative research approach, data were collected using an online questionnaire from a sample of 416 respondents. Data analysis was conducted utilizing Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) The findings revealed that the developed causal relationship model, comprising four main constructs—Service Quality, Perceived Value, Satisfaction, and Loyalty—demonstrated a good fit with the empirical data. Service Quality and Perceived Value exhibited the highest direct effects on Loyalty regarding the purchase of Mutelu cosmetics, respectively. Furthermore, both variables exerted a significant indirect effect on Loyalty through Satisfaction, which functioned as the primary mediator. The conclusion suggests that the success of Mutelu cosmetic businesses in the digital era depends heavily on prioritizing prompt and comprehensive service quality as a core driver of customer loyalty alongside with enhancing the perception of price-value and overall satisfaction to retain a long-term customer base. The results of this study provide valuable insights for entrepreneurs in formulating effective marketing strategies to foster sustainable consumer loyalty.